Warriors and other men : notions of masculinity from the late Bronze Age to the early Iron Age in Scandinavia - Skogstrand, Lisbeth, (Archaeopress, 2016)
This text questions whether androcentric archaeology has taught us anything about prehistoric men and their masculinities.